The Effect of Hours Constraints on Labor Supply Estimates - Kahn, Shulamit; Lang, Kevin (The Review of Economics and Statistics, 1991)
Almost all labor-supply models are estimated under the assumption that workers are free to choose their hours. However, theory, casual empiricism, and survey data suggest that many workers are not free to vary the hours within a job. Consequently, labor-supply estimates based on actual hours of work may be biased. Using Canadian data on desired hours of work, the authors find that using actual hours causes labor-supply estimates to be biased upwards. Copyright 1991 by MIT Press.